Advancing sino-US relations: putting agriculture first - Zhang, Hongzhou (2014)
Notwithstanding the remarkable progress in agricultural cooperation between China and US, potential threats lie ahead. Still expanding agricultural ties can be the ballast in advancing Sino-US relations.